HUBUNGAN KOORDINASI MATA–TANGAN DENGAN PASSING BAWAH DALAM PERMAINAN BOLAVOLI MINI SISWA KELAS V SDN 009 BANGKINANG - Wijayanti, Ni Putu Nita; ', Rhodiati; ', Slamet (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s observation of student in class V SDN 009 of Bangkinang. Researcher found discovered a weakness of under passing. It can be seen from some of the mtches have been followed. The purpose of this research is to the corelation hand-eyes coordination with under passing of mini vollyball of student in class V SDN 009 of Bangkinang. Population in this research were all students in class V SDN 009 of Bangkinang amount 22 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 22 people. Research instrument measure hand-eyes coordination test and under passing test. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : there is corelation hand-eyes coordination with under passing of mini vollyball of student in class V SDN 009 of Bangkinang.Key word : hand-eyes coordination, under passing